Inflammation, a Link between Obesity and Cardiovascular Disease - Zhaoxia Wang; Tomohiro Nakayama (Hindawi Limited, 2010)
Obesity, the most common nutritional disorder in industrialized countries, is associated with an increased mortality and morbidity of cardiovascular disease (CVD). Obesity is primarily considered to be a disorder of energy balance, and it has recently been suggested that some forms of obesity are associated with chronic low-grade inflammation. The present paper focuses on the current status of our knowledge regarding chronic inflammation, a link between obesity and CVDs, including heart diseases, vascular disease and atherosclerosis. The paper discusses the methods of body fat evaluation in humans, the endocrinology and distribution of adipose tissue in the genders, the pathophysiology of obesity, the relationship among obesity, inflammation, and CVD, and the adipose tissue-derived cytokines known to affect inflammation. Due to space limitations, this paper focuses on C-reactive protein, serum amyloid A, leptin, adiponectin, resistin, visfatin, chemerin, omentin, vaspin, apelin, and retinol binding protein 4 as adipokines.